Synthesis, characterization and application of doped-polyaniline (pani) nanocomposites for microwave absorption / Koh Yen Nee - Koh, Yen Nee (2014)

(untitled)
Conducting polymer nanocomposites containing aniline (Ani) monomer and hexanoic acid (HA) dopant has been synthesized by template free method. Dielectric (titanium dioxide (TiO2)) and magnetic (iron (III) oxide (Fe3O4), carbon nanotubes (CNT), graphene and etc.) materials have been added to improve the dielectric and magnetization property of the nanocomposites. Fourier Transform Infra Red (FTIR), Ultraviolet-visible (UV-vis), and X-ray diffraction (XRD) analyses have confirmed the chemical structure of the doped-polyaniline (PAni) nanocomposites. Morphology study, thermal behavior, electrical conductivity and magnetic behavior of the nanocomposites have been investigated by Field Emission Scanning Electron Microscope (FESEM), Thermal Gravimetric Analyzer (TGA), resistivity meter and vibrating samples magnetometer (VSM), respectively. Microwave absorption study was carried out by Microwave Vector Network Analyzer (MVNA) from 0.5 to 18 GHz. In this research study, four types of PAni nanocomposites were prepared namely PAni/HA/TiO2/Fe3O4 nanocomposites (with and without chemical treatments), PAni/HA/TiO2/MWNT nanocomposites (different diameter and length of MWNT), PAni/HA/TiO2/DWNT nanocomposites (different contents of u-DWNT and c-DWNT) and PAni/HA/TiO2/GNP nanocomposites (different contents of GNP). In general, high electrical conductivity, dielectric permittivity and magnetic permeability are the few factors that will contribute to a better microwave absorption property of a material. Among all PAni nanocomposites, PAni/HA/TiO2/MWNT nanocomposites with MWNT (D = 10-20 nm, l = 5-15 μm) possesses the highest reflection loss (RL = -58 dB) at 7 GHz due to the high heterogeneity and high μrʹ′ and μrʹ′ʹ′. This significantly induces the space charge polarization and eddy current along the PAni backbone. Finally, it indicates the strongest absorption. This material is potentially applied as a good iv microwave absorber in computer, which operate at 7 GHz. However, PAni/HA/TiO2/GNP nanocomposites with 40 % of GNP possesses the poorest microwave absorption with RL of -6.6 dB due to the lower value of μrʹ′ and μrʹ′ʹ′ and the absent of the nanorods/nanotubes (without heterogeneity). Thus, it significantly impedes the interaction between PAni and GNP, and eventually leads to the weakest microwave absorption.